2023
DOI: 10.3389/fnins.2023.1121043
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent theta burst stimulation vs. high-frequency repetitive transcranial magnetic stimulation for post-stroke cognitive impairment: Protocol of a pilot randomized controlled double-blind trial

Abstract: IntroductionIntermittent theta burst stimulation (iTBS), a novel mode of transcranial magnetic stimulation (TMS), has curative effects on patients with post-stroke cognitive impairment (PSCI). However, whether iTBS will be more applicable in clinical use than conventional high-frequency repetitive transcranial magnetic stimulation (rTMS) is unknown. Our study aims to compare the difference in effect between iTBS and rTMS in treating PSCI based on a randomized controlled trial, as well as to determine its safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Previous evidence has shown that routine high-frequency rTMS promotes neurogenesis in the human motor cortex more effectively than in rat models 32 . iTBS has also been shown to have a significant role in reducing cognitive dysfunction after stroke 33 . These findings further confirm the role of iTBS in improving cognitive function and the role of rTMS in enhancing cognitive function in MDD, and may explain why the treatment effect and ERP changes were more significant in the CT group than the DT group in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has shown that routine high-frequency rTMS promotes neurogenesis in the human motor cortex more effectively than in rat models 32 . iTBS has also been shown to have a significant role in reducing cognitive dysfunction after stroke 33 . These findings further confirm the role of iTBS in improving cognitive function and the role of rTMS in enhancing cognitive function in MDD, and may explain why the treatment effect and ERP changes were more significant in the CT group than the DT group in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Test power 1-β = 0.95. Using G*Power3.1.9.7 software and single factor analysis of variance in the F test ( 27 , 28 ), the required sample size of n = 87 cases was calculated, and the shedding rate was set at 10%. The total sample size was 96 cases, and the required sample size for each group was 32 cases.…”
Section: Methodsmentioning
confidence: 99%
“…No consensus currently exists regarding the superiority of either conventional rTMS or iTBS for treating patients with PSCI. Therefore, we aimed to examine the variations between iTBS and rTMS in PSCI patients [ 70 ], using fNIRS to study the neural activity changes induced by each intervention. In doing so, we aimed to establish a theoretical foundation for clinical application.…”
Section: Nirs As An Assessment Toolmentioning
confidence: 99%